Evaluasi Geometri Jalan Menggunakan Uav Dengan Aplikasi Agisoft Photoscanner Pada Jalan Meranti Kampus IPB Dramaga - Dhia Kamal Irfan; Sutoyo Sutoyo; Tri Sudibyo (Jurnal Teknik Sipil dan Lingkungan, 2020)
There are various road construction projects in Indonesia, but most of these projects still use conventional methods in evaluating road geometry. This study aims to evaluate the geometry of the road using UAV and analyze the accuracy and accuracy of photogrammetry in the evaluation of road geometry. This research took place at Dramaga's IPB Campus on Meranti street and was conducted from April to July 2019. From a series of processes that have been carried out it can produce accuracy of measuring 97,243% and 98,296% across the road for orthophoto results without and with coordinate correction and using GCP. For accuracy in this study obtained a value of 0.858 m so that it can be concluded that the data processing map is included in the class 3 horizontal accuracy. The horizontal alignment parameters analyzed in this study are bend angles, turn radius, and turn length, there are two curves analyzed. For the value of each parameter each turn successively for data without coordinate correction and elevation is 149 °; 90 °; 40.61 m; 53.75 m; 23.39 m; 90.71 m. The results of horizontal alignment analysis for data with coordinate correction are 150 °; 88 °; 30.81 m; 49.34 m; 21.39 m; 89.3 m. The vertical alignment analyzed in this study has two parameters, namely vertical curvature and slope. The value of the analysis results for the two parameters of the two points for results with correction and without correction of coordinates are 16.08%, 17.22%, 53 m, 51 m and 6.88%, 3.77%, 53 m, and 51 m .